Investigation and reduction methods of specific absorption rate for biomedical applications: A survey. Issue 3 (1st December 2017) - Priyadarshini, S. Jemima; Hemanth, D. Jude
Abstract: Specific Absorption Rate (SAR) is an inevitable parameter to be considered for various RF dosimetry evaluations in the field of biomedical engineering. There is a much concern in exposure studies as they have a significant impact on the social and health issues in the recent global community. SAR measures the absorption of electromagnetic radiation of RF from devices in an exposure area. The significance of SAR parameter has been awakened in broad areas of technology and even considered in the design of radiating structures from biomedical devices such as MRI to also popular mobile phones. Researchers have explicated the constant interaction of electromagnetic field interactions with biological systems. The advancements in technology pose a grave concern about the impact on human health. This paper intends to undertake an extensive survey of the various current investigations done with SAR in different scenarios with possible radiating structures and also focus on exposure areas on the human body. The SAR depends on estimation parameters that are analyzed and discussed. Further, the paper will analyze comparatively the facets of implied Methodologies in SAR computation. The parametric evaluation of SAR paves the way for a requirement reduction of SAR parameter. The paper discusses current reduction methodologies and its primary advantages and details possible setbacks. The analysis indicates a requirement of the specific radiation structure for a particular area of exposure of concern, followed by a need of ideal reduction methodology.